The role of endoscopic ultrasound-guided fine-needle aspiration/biopsy in the diagnosis of mediastinal lesions - Zhou, Jingjing; Cai, Ting; Wu, Dongwen; Chen, Xiong; Wang, Fen (Frontiers in Surgery, 2023)
Objective: Endoscopic ultrasound-guided fine-needle aspiration/biopsy (EUS-FNA/FNB) is an accurate technique for sampling the pancreas and mediastinum. The aim of this study was to determine the value of EUS-FNA/FNB in the diagnosis of mediastinal lesions. Methods: Data from 107 patients who underwent EUS-FNA/FNB for mediastinal lesions were evaluated. Results:The sensitivity, specificity, positive predictive value, and negative predictive value of EUS-FNA/FNB for mediastinal lesions were 92.00%, 100%, 100%, and 85%, respectively. The sensitivity, specificity, positive predictive value, and negative predictive value of EUS-FNA for malignant mediastinal lesions were 92.00%, 100%, 100%, and 86.00%, respectively. The sensitivity, specificity, positive predictive value, and negative predictive value of EUS-FNB for malignant mediastinal lesions were 92.00%, 100%, 100%, and 82.00%, respectively. Except for the discomfort caused by conventional gastroscopy, none of the patients had any complications, such as damage to surrounding large blood vessels or nerves. Conclusion: EUS-FNA/FNB is an effective tool for diagnosing unknown mediastinal lesions, without any obvious complications.